WAKAF TUNAI SEBAGAI POTENSI PENGEMBANGAN EKONOMI DI INDONESIA Sebuah Analisis antara Peluang dan Tantangan - Djakfar, Muhammad (Fakultas Ekonomi, UIN Maliki Malang, 2007)
Several instruments in Islam are prospectively developed to establish social awarness. Cash waqf, for instance, is a promising economic unit although it is considered alien in Islamic community . In Indonesia, it is a potential source to increase the economic welfare. As a solution to economic crisis, cash waqf is a way to dig up financial source. Muslim may help the nation escape from economic turbulence as well as they show their obedience to God via charity. Different from the traditional concept of waqf which is dominantly associated to hectares of land, cash waqf does not necessarily need huge capital. Īt is only a sum of money which is allocated to an Islamic institution for communal development. Besides these opportunities, some problems are faced. People have not been well informed about the idea of cash waqf. This challenge should be solved by continuous socialization, particularly to waqif (waqf doer) candidate and nadzir (waqf organizer). Cash waqf arrangement is also important to raise welfare of society. Government with its political will has offered several alternatives to improve cash waqf, such as establishing waqf institution and opening waqf network.